Perfil Victimológico De Mujeres Que Son Engañadas Y Perecen En Las Redes De Delincuentes Informáticos (2019)
Affection can be considered as a two-sided emotion, since by means of this one can be affected or benefited a person. In the case of cybercrime, affectivity becomes a tool for criminals in order to obtain a benefit, they get it through cheating women who currently go through complex emotional situations. The present degree work sought to identify a psychosocial profile of women who are deceived by computer criminals. To identify them, an investigation was carried out in which five women previously victims of deceit were involved.